2015
DOI: 10.7314/apjcp.2015.16.4.1471
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dose Dense Doxorubicin and Cyclophosphamide Followed by Paclitaxel versus Conventional Dose Doxorubicin, Cyclophosphamide Followed by Paclitaxel or Docetaxel in Patients with Node-Positive Breast Cancer

Abstract: Breast cancer is the most commonly diagnosed cancer type and is the second leading cause of death due to cancer among women all over the world and breast cancer alone is expected to account for 29% of all new cancers among women (Siegel et al., 2014). However, surgery is the only curative treatment modality of early breast cancer patients, adjuvant systemic chemotherapy following surgery have significant effect on disease free survival Afterunivariate and multivariate analysis were performed, 3-year DFS rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…After that, NUSAP1 gradually became the focus in various tumor research. Brinkley found that spindle defects lead to genomic instability in invasive tumor cells with NUSAP1 loss [19]. Raemaekers found that NUSAP1 is localized in the nucleus and spindle and is over-expressed in proliferating cells in phase G2/M, resulting in spindle bundle bundling and inhibiting cell proliferation [18].…”
Section: Discussionmentioning
confidence: 99%
“…After that, NUSAP1 gradually became the focus in various tumor research. Brinkley found that spindle defects lead to genomic instability in invasive tumor cells with NUSAP1 loss [19]. Raemaekers found that NUSAP1 is localized in the nucleus and spindle and is over-expressed in proliferating cells in phase G2/M, resulting in spindle bundle bundling and inhibiting cell proliferation [18].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of severe peripheral neuropathy in our patients was relatively higher (4 vs. 27) than reported in other randomized controlled trials. 38,39 During the treatment with AC regimen and AC part of the AC-T regimen, our study participants reported only mild peripheral neuropathy compared to randomized controlled trials. 40 Hence, the cumulative dose of AC chemotherapy might increase the risks of paclitaxelinduced severe peripheral neuropathy later.…”
Section: Discussionmentioning
confidence: 85%
“…Breast cancer is the most frequently diagnosed cancers and the leading causes of cancer death in women , and approximately one-third of breast cancer cases are expected to occur in women <50 years of age (Siegel et al, 2015). Chemotherapy has been the mainstay of adjuvant therapy for premenopausal women with node-positive breast cancer, and its effect was much higher in younger women than in older women (Yazilitas et al, 2015). The benefit of adjuvant chemotherapy has been supposed that at least part of it is derived from chemotherapyinduced ovarian ablation.…”
Section: Introductionmentioning
confidence: 99%